Transcriptional activity of tumour necrosis factor α (TNF-α) in patients with subclinical coronary atherosclerosis - preliminary results - Dabek, J; Swiderski, R; Głogowska-Ligus, J; Pysz, P (Folia biologica (Praha), 2012)
The most frequent cause of ischaemic heart disease is coronary arteriosclerosis. This study was aimed at assessing gene expression of TNFA and its two receptors (TNFR1, TNFR2), as well as determining coronary artery calcium score (CACS) in the context of occurrence of classical risk factors in patients with subclinical atherosclerosis of coronary vessels. The study involved 47 subjects with complaints of chest pain and suspicion of acute coronary syndrome or stable coronary disease. Additionally, CACS was assessed by 64-slice computerized tomography. QRT-PCR molecular studies were performed using RNA isolated from peripheral blood mononuclear cells. Preliminary results of molecular studies on patients with subclinical coronary atherosclerosis revealed a significantly lower numbers of TNFR1 and TNFR2 gene copies as compared with healthy subjects. In addition, it can be demonstrated that among classical risk factors hypertension is of substantial importance in the progression of coronary arteries' calcification, and that in the examined group CACS increases together with the rising number of classical risk factors involved. No correlation was observed, however, between expression of TNFA, TNFR1 and TNFR2 genes and the value of CACS. Conclusions: 1. The occurrence of hypertension facilitates initiation and progression of arteriosclerotic lesions in blood vessels including the coronary ones; the raised number of circulatory disease classical risk factors involved correlates with elevated calcification of coronary arteries as shown by 64-slice computerized tomography scans. 2. Significantly decreased numbers of TNFR1 and TNFR2 gene copies observed in the investigated group may play a significant role in initiation and progression of arteriosclerosis.
Keywords: genetická transkripce; nemoci koronárních tepen; Calcium; Coronary Artery Disease; Receptors, Tumor Necrosis Factor, Type I; Humans; lidé středního věku; regulace genové exprese; Transcription, Genetic; koronární cévy; Coronary Vessels; vápník; rizikové faktory; Aged; dospělí; Female; senioři; lidé; receptory TNF - typ II; TNF-alfa; Adult; ženské pohlaví; Gene Expression Regulation; Male; Receptors, Tumor Necrosis Factor, Type II; Middle Aged; Genetic Predisposition to Disease; genetická predispozice k nemoci; Tumor Necrosis Factor-alpha; receptory TNF - typ I; mužské pohlaví; Risk Factors